Капнометрія дозволяє покращити "респіраторну" безпеку пацієнтів з ожирінням після операцій на органах черевної порожнини - Воротинцев, Сергій Іванович; Воротынцев, С. И.; Vorotyntsev, S. І. (My University, 2016)
В роботі проведене дослідження інцидентності депресії дихання у хворих з ожирінням, оперованих на органах черевної порожнини. За допомогою капнометрії виявлено, що випадки клінічно значущої післяопераційної гіповентиляції виникають у всіх пацієнтів з ожирінням, але частіше при використанні тотальної внутрішньовенної анестезії і призначенні наркотиків для знеболення після операції, ніж при застосуванні комбінованої епідурально-загальної анестезії з пролонгацією знеболення місцевими анестетиками. Показано, що коли у хворих із ожирінням в найближчому післяопераційному періоді використовується кисень, капнометрія може допомогти у виявленні «субклінічної» депресії дихання та визначенні зупинок дихання під час сну, гарантуючи таким чином «респіраторну» безпеку пацієнтів. В работе проведено исследование инцидентности депрессии дыхания у больных с ожирением, оперированных на органах брюшной полости. С помощью капнометрии выявлено, что случаи клинически значимой послеоперационной гиповентиляции возникают у всех пациентов с ожирением, но чаще при применении тотальной внутривенной анестезии и назначении наркотиков для обезболивания после операции, чем при использовании комбинированной эпидурально-общей анестезии с пролонгацией обезболивания местными анестетиками. Показано, что когда у больных с ожирением в ближайшем послеоперационном периоде применяется кислород, капнометрия может помочь в выявлении «субклинической» депрессии дыхания и определении остановок дыхания во время сна, гарантируя таким образом «респираторную» безопасность пациентов. The CO2 control in the end of exhalation of patients with general anesthesia significantly reduces the quantity of complications, connected with ventilation as during surgery as in postoperative period. Respiratory depression after surgery depends on the patients’ age, surgery type and kind of aneasthesia, the use of opioids for pain relief, the presence of related pathology. Obese patients worth special attention, because the risk of postoperative hypoventilation and hypoxya is much higher among them, and opioids prescription to patients with obstructive sleep apnea (OSA) can cause even respiratory arrest and death. Therefore it is considered that monitoring of ETCO2 of patients with obesity and OSA in early postoperative period can reduce the risk of respiratory complications. We made a prospective one-center research for evaluation of capnometry as a method of respiratory monitoring after abdominal surgery in 60 patients with obesity. Depending of the type of anesthesia all patients were divided to 2 groups: total intravenous anesthesia (TIVA, n=30) and combined epidural-general anesthesia (CEGA, n=30). All patients were extubated in operating theatre and transferred to postoperative room of surgery department, where they were getting oxygen through nasal cannula with a speed 4 l/min and it was provided to them monitoring of SpO2, pulse rate, blood pressure, ETCO2 and respiratory rate during 2 hours. The end points of research were: time of tracheal extubation after the end of surgery; amount of dyspnea in first 10 minutes after extubation; time of safe transfer to the ward; cases of ventilation violations according to the data of deviation from established triggers (SpO2<92%, RR<8/min, ETCO2>50 mm Hg, ETCO2<30 mm Hg, apnea time >20 sec.); quantity of postoperative lungs complications; duration the stay in hospital. Statistical analysis of the results was provided with a program Statistica for Windows version 6.0. Data presented as mean ± standard deviation with a normal division of data, median and quartiles — with abnormal.
Капнометрия позволяет улучшить «респираторную» безопасность пациентов с ожирением после операций на органах брюшной полости
Capnometry improves «respiratory» safety of obese patients after abdominal surgery
Keywords: ожиріння; абдомінальна хірургія; післяопераційна гіповентиляція; капнометрія; ожирение; абдоминальная хирургия; послеоперационная гиповентиляция; капнометрия; obesity; abdominal surgery; postoperative hypoventilation; capnometry